The Analysis of Structural Equation Modeling of Organizational Strategy in Disruption Period, Catholic Identity and Organizational Performance of Catholic Private Schools - Jurod, Somkiat; Sucharitrak, Phornsak; Parangkul, Chuan (Scholar: Human Sciences, 2024)
Purpose: This research explored the organizational strategy in the disruption period, Catholic identity, and organizational performance of Catholic private schools. Exploratory factor analysis, confirmatory factor analysis, and structural equation modeling were performed to determine the causal effect between the model. Research design, data and methodology: The data was collected using a 5-rating scale questionnaire from 155 Catholic private schools in Thailand with 305 respondents and was valid and reliable (=0.989). Result: The organizational strategy in the disruption period found seven components: (1) learning and teaching; (2) practical plan of strategies; (3) leadership and school culture; (4) assessment; (5) school partners; (6) curriculum; and (7) professional teacher. At the same time, Catholic Identity has two components: (1) the characteristics of Catholic schools; and (2) the nature of Catholic schools. Furthermore, organizational performance found five components: (1) school culture and climate of learning; (2) personal leadership; (3) talent management; (4) planning and operation of schools; and (5) measurement and quality assessment of learning management. Conclusion: The organizational strategy in the disruption period had the most significant total influence on organizational performance, rather than indirect influence through Catholic identity. While Catholic identity had a total and direct influence on organizational performance. Furthermore, organizational strategy in the disruption period had a total and direct influence on the Catholic identity.